(3Ohd GdESdGe GdTQja GdHgjI hPcQ eG XgQ di ef Mce Gddg GdNajI aj LdH WGFaI GdCJQGc Edi GdOjGQ GdeUQjIs - (3eMeO GdbOSj GdTGaYj, CHh MGeO,J (B893 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jRhd edcg hdG jZfi s
(3jdjg ef U (B63 (3Edi (B70 (3JGQjN GdNdaGA ajgi PcQ GdNdaGA Edi eYJUe hgh eNJUQ eLghd eDdags
(3ahJhZQGa ef fSNI HNW bOjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B134 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs